Estimation of Specific Yield for Regional Groundwater Models: Pitfalls, Ramifications, and a Promising Path Forward. Issue 1 (10th January 2022) - Liu, Gaisheng; Wilson, Blake B.; Bohling, Geoffrey C.; Whittemore, Donald O.; Butler, James J.
Abstract: Specific yield (Sy) is one of the most important aquifer parameters in groundwater models with large storage changes. However, it has received limited attention from the modeling community and there are few, if any, approaches that can be widely applied for determination of Sy at the scale required for regional aquifer studies. Despite the limitations of parameter estimation methods and of direct measurements of aquifer storage properties in the field, the large uncertainty in model Sy values is typically ignored and Sy is incorrectly assumed to be a known quantity. These practices can introduce errors into model predictions of aquifer budget components, such as recharge and storage depletion. In turn, aquifer management and planning can be greatly impacted, as estimates of aquifer responses to pumping changes are highly dependent on those simulated budget components. In this work, we use a groundwater model of a portion of the High Plains aquifer in the central United States to illustrate the impacts of inappropriately large Sy values on model predictions and the related water management ramifications. Building on our recent work, we propose a data‐driven approach for determining specific yield for regional groundwater models. Results demonstrate that this new approach can improve model reliability and lead to more robust predictions of aquifer responses to management scenarios. Key Points: Specific yield values are uncertain in many models of unconsolidated aquifers Models with inappropriate specific yield values can produce unreliable aquifer budgets and responses under future management scenarios A new approach is proposed for estimating the spatial distribution of specific yield for regional groundwater models